2016
DOI: 10.1139/cjss-2015-0136
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of forest management effects on the mineral soil carbon pool of a lowland, mixed-species forest in Maine, USA

Abstract: Concerns about climate change have increased interest in ways to maximize carbon (C) storage in forests through the use of alternative forest management strategies. However, the influence of these strategies on soil C pools is unclear. The primary objective of this study was to test for differences in mineral soil C stocks among various silvicultural and harvesting treatments that were initiated in the 1950s and have been maintained since on the Penobscot Experimental Forest in central Maine, USA. Five mineral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…In the Northeastern United States, partial and complete harvesting treatments (light thinning, heavy thinning and clearcutting) were reported to have no effect on forest floor and mineral soil C (Hoover, 2011). Similarly, a study in a lowland mixed species stand found no difference in mineral soil C stocks following selection, shelterwood and clearcutting treatments (Puhlick et al, 2016). All of these findings suggest that a less intense management action could be considered in stands where maintaining and/or increasing soil C stocks is of interest (Jandl et al, 2007;Powers et al, 2012).…”
Section: Forest Soil C: Considerations and Knowledge Gapsmentioning
confidence: 99%
“…In the Northeastern United States, partial and complete harvesting treatments (light thinning, heavy thinning and clearcutting) were reported to have no effect on forest floor and mineral soil C (Hoover, 2011). Similarly, a study in a lowland mixed species stand found no difference in mineral soil C stocks following selection, shelterwood and clearcutting treatments (Puhlick et al, 2016). All of these findings suggest that a less intense management action could be considered in stands where maintaining and/or increasing soil C stocks is of interest (Jandl et al, 2007;Powers et al, 2012).…”
Section: Forest Soil C: Considerations and Knowledge Gapsmentioning
confidence: 99%
“…These PSPs were selected in a random, 187 stratified process, with stratification according to the proportion of major soil types on glacial till 188 within each replicate (Puhlick et al 2016a). Species and dbh were recorded for each tree and shrub, and biomass in woody portions shrub biomass as "live tree biomass" throughout the remainder of the manuscript.…”
mentioning
confidence: 99%
“…The mutually consistent O horizon increase in our two observational datasets, one of which (the soil survey pedon dataset) samples by horizon and the other of which (the national forest inventory dataset) samples by a horizon / depth hybrid approach, may imply that there may be functional interactions between soil horizons. However, as discussed in the prior paragraph, we discount these results due to the potential for spatial design problems, which should be expected in a region where a large share of the harvesting is done in northern coniferous forest types with large O horizon C stocks [ 42 , 44 , 73 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, we incorporated bulk density (Db) as a specific response parameter of interest. Second, in several cases, we directly contacted study authors to obtain data not reported in, but underpinning several forest harvest papers from the region [ 73 , 83 , 84 , 87 , 88 ]. These personal communications were necessary to bring summarized data from these important regional papers to the same level of site-specific detail found in the majority of other forest harvest papers (or their associated Additional file 2 : Datasets).…”
Section: Methodsmentioning
confidence: 99%